2011
DOI: 10.1007/s11295-011-0380-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the genus Malus and implications for linkage mapping with SNPs

Abstract: Knowledge about the sequence-based genetic diversity of a crop species is important in order to develop highly informative genotyping assays, which will eventually positively impact breeding practice. Diversity data were obtained from two pools of 185 and 75 accessions each, representing most of the species belonging to the genus Malus, by re-sequencing 27 gene-specific amplicons and by screening 237 Malus × domestica SNPs using the multiplex genotyping technology SNPlex™. Nucleotide diversity and insertion/de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
4
39
2
Order By: Relevance
“…Although, probabilistically, the expected proportion between transitions and transversions is 1:2, a bias towards transitions is frequently observed, probably as a consequence of greater purifying selection against transversions (Keller et al 2007) that may vary for different organisms (Strandberg and Salter 2004). The transition/transversion ratio observed here (1.77) is similar to that observed in grape (1.56 by Salmaso et al 2004 and1.46 by Lijavetzky et al 2007) and potato (1.5 by Simko et al 2006) and higher than that observed in apple (1.27 by Micheletti et al 2011). The number of polymorphic sites in polymorphic loci (including SNPs and indels) varied from one to six, with an average of 2.3 (Table 4).…”
Section: Sequence Variabilitysupporting
confidence: 88%
See 2 more Smart Citations
“…Although, probabilistically, the expected proportion between transitions and transversions is 1:2, a bias towards transitions is frequently observed, probably as a consequence of greater purifying selection against transversions (Keller et al 2007) that may vary for different organisms (Strandberg and Salter 2004). The transition/transversion ratio observed here (1.77) is similar to that observed in grape (1.56 by Salmaso et al 2004 and1.46 by Lijavetzky et al 2007) and potato (1.5 by Simko et al 2006) and higher than that observed in apple (1.27 by Micheletti et al 2011). The number of polymorphic sites in polymorphic loci (including SNPs and indels) varied from one to six, with an average of 2.3 (Table 4).…”
Section: Sequence Variabilitysupporting
confidence: 88%
“…2). This contrasts with allele frequencies observed in species more variable than peach, such as apple, with 26-42 % of alleles with MAF>0.2 after re-sequencing two different sets of M. x domestica germplasm (Micheletti et al 2011). Our results suggest that a large proportion of the SNPs discovered on sequencing peach occidental germplasm will be useful for association mapping purposes, where MAF is usually set at ≥5 %, as well as for inclusion in large-scale genotyping platforms, where only robust SNPs are desired.…”
Section: Sequence Variabilitycontrasting
confidence: 67%
See 1 more Smart Citation
“…Sequencing of the complex heterozygous genome of the apple cultivar 'Golden Delicious' ) has led to the discovery of many thousands of DNA polymorphisms (about 4.4 single nucleotide polymorphisms (SNPs) per kilobase (kb)). Some other recent reports indicated an occurrence of one SNP every 149 bp within coding sequences of 'Royal Gala' , and one SNP every 52 bp in the wider Malus germplasm (Micheletti et al 2011). A practical goal of sequencing was to accelerate the breeding of this economically important perennial crop species.…”
Section: Introductionmentioning
confidence: 99%
“…Research was initiated to define the position of resistances that had not been fine-mapped satisfactorily (Rvi2, Rvi4 and Rvi11), and to develop cost-effective genetic markers for high-throughput screening of all the resistances listed. For this last purpose, SNP markers seemed most suitable because of their high frequency (between 4.5 and 20 markers/ kbp) in the apple genome (Velasco et al 2010;Micheletti et al 2011) and coupled with the availability of technologies enabling the simultaneous genotyping from a few to thousands of markers per DNA sample. The resistance genes Rvi6, Rvi15, Pl2 and FB_MR5 have been cloned in the last decade (Belfanti et al 2004;Schouten et al 2014;Rikkerink et al 2007;Broggini et al 2014), while for FB_E, positional cloning is in progress (Parravicini et al 2011).…”
Section: Introductionmentioning
confidence: 99%